ASSESSING TAX AWARENESS AMONG UNDERGRADUATE STUDENTS OF UNIVERSITY TEKNOLOGI MARA: A STUDY ON ATTITUDE, MORAL, KNOWLEDGE & PERCEPTION TOWARDS TAX AUTHORITIES - Safian, Noorliana; Shahid, Khairiyah Md; Hamid@Hussain, Shawal Sahid; Ngah, Nor Syamaliah; Merican, Farah Murni; Abd Aziz, Norazlin; Hussain, Azlin Mohd (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
This study investigates the factors influencing tax awareness among undergraduate students at Universiti Teknologi MARA (UiTM), with particular emphasis on tax knowledge, attitudes, morale, and perceptions of tax authorities. Grounded in the Theory of Planned Behaviour (TPB), the research explores how these elements shape students’ intentions and behaviours regarding tax compliance. Employing a quantitative approach, data were collected through a cross-sectional survey administered to a representative sample of 384 undergraduate students. The findings reveal that tax knowledge and positive attitudes towards taxation significantly enhance tax awareness, reinforcing previous literature that highlights the critical role of education in fostering compliance. Moreover, students' perceptions of the role and effectiveness of tax authorities were found to substantially influence their tax morale and intentions to comply. These results suggest that integrating comprehensive tax education into university curricula and enhancing the visibility and accessibility of tax authorities may meaningfully improve future taxpayers' awareness and compliance. The study offers valuable insights for policymakers and educational institutions aiming to cultivate a more informed and compliant taxpaying population in Malaysia.